Trades-Related Post-Secondary Educational Attainment among Immigrant and Canadian-Born Young Adults in Alberta (Alberta Journal of Educational Research, 2013)
This paper examines trades-related and university educational attainment (by age 25) of immigrant and Canadian-born Alberta youth while controlling for gender, family socio-economic status, high school grades, and parental encouragement regarding higher education. Data from the longitudinal Alberta School-Work Transitions Study (1996 – 2003) reveal significant differences between immigrants and non-immigrant young adults in terms of trades-related post-secondary education (PSE). Multinomial logit analysis shows that Alberta immigrant youth are significantly more likely than their Canadian-born counterparts to attain trades-related PSE credentials by age 25. Important factors explaining these differences include parental encouragement and high school grades. Cet article porte sur les réalisations relatives aux métiers et à l’éducation universitaire avant l’âge de 25 ans chez de jeunes immigrants d’une part et de jeunes albertains nés au Canada d’autre part. L’étude tient compte du sexe, du statut socioéconomique de la famille, des notes au secondaire et de l’appui parental en ce qui touche l’enseignement supérieur. Les données provenant d’une étude longitudinale albertaine portant sur le passage de l’école au travail (Alberta School-Work Transitions Study 1996 – 2003) révèlent des différences significatives entre les jeunes adultes immigrants et non-immigrants quant à l’éducation postsecondaire associée aux métiers. Une analyse logit multinomiale démontre que les jeunes albertains immigrants sont nettement plus susceptibles que leurs homologues nés au Canada à obtenir un diplôme d’éducation postsecondaire associée aux métiers avant l’âge de 25 ans. Parmi les facteurs importants qui expliquent ces différences notons l’appui parental et les notes au secondaire.